The Worship of God Agni in the Ngekehin Tradition - Dewi Rahayu Aryaningsih; I Gusti Ngurah Sudiana; I Wayan Wastawa (LITERACY : International Scientific Journals of Social, Education, Humanities, 2024)
Names are essential in society, with interactions starting by mentioning names. Parents give names to their children differently across regions, tribes, and clans, often involving rituals and traditions. The Hindu community of West Lombok Regency has a naming tradition called Ngekehin, performed for babies who are 12 or 42 days old. This unique tradition uses 11 rolled papers with different names stuck in ash and pis bolong within a tamas. The Ngekehin tradition is still practiced across generations, though many do not understand its theological significance. Qualitative research, involving primary and secondary data sources, was conducted to gather information. Informants were selected through purposive sampling, and data collection methods included observation, interviews, and documentation. Research shows that the upakara procession in Ngekehin holds many meanings, particularly theological. The rolling fire in the tradition implies worship of Lord Agni, a deity revered since the Vedic era. In Ngekehin, Lord Agni serves as: 1) The leader of the naming ceremony, 2) An intermediary between the worshipper and the Almighty, giving a "sign" through the lintingan fire indicating the suitable name, chosen from the first or last burning lintingan, 3) A witness to the chosen name, 4) A purifier of mala/impurities since the 12-day baby ceremony is the first "cleansing" in the life cycle, and 5) A remover of previous karmawasana sins.